Pure bilateral endodermal sinus tumor in a female case of Ullrich-Turner syndrome with 45,X/46,XY karyotype - Etem, Ebru Onalan; Yuce, Huseyin; Celik, Husnu; Dagli, Ferda; Elkiran, Tamer (Galenos Yayincilik, 2009)
The presence of mosaic 45,X/46,XY is a very rare chromosomal anomaly. The presence of Y chromatin in individulas with Ullrich-Turner syndrome confers a risk for gonadoblastoma. The case presented with short stature, primary amenorrhea and a hypoplasic uterus. Karyotype was determined as 45,X/46,XY by cytogenetic analysis of peripheral blood. We performed molecular genetic analysis for Y chromosomal loci (SRY, ZFY, SY84, SY86, SY127, SY134, SY254, SY255) in both blood leukocytes and paraffin-embedded gonadal tissue. The case was positive for all sequences tested and developed an bilateral endodermal sinus tumor diagnosed by a pathologist. Adequate counseling regarding gonadectomy should be given because of the high proportion (33%) of gonadal tumors in patients with Y-chromosome sequences. It is the first report about bilateral EST in a UTS patient with 45,X/46XY karyotype to our knowledge.
Keywords: Ullrich-Turner syndrome; Y chromosomal loci; endodermal sinus tumor